STRATEGI KOMUNIKASI PARIWISATA DALAM PENGEMBANGAN OBJEK WISATA PANTAI OLEH DINAS PARIWISATA DAN KEBUDAYAAN DI PULAU PANGERAN KABUPATEN KEPULAUAN ANAMBAS - Rianty Ellsa; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Pangeran Island is a relatively new tourist destination and currently being developed by Department of Tourism and Culture in one of the villages, namely Belibak Village, Anambas Islands Regency is one area that has natural tourism potential that can be presented as a leading tourism destination. Anambas Islands Regency. Of course, in carrying out development, it is inseparable from the communication strategy carried out by the Department of Tourism and Culture. The purpose of this study was to determine the strategy of selecting communicators, compiling messages, selecting media and determining audiences. This study used qualitative research methods. The research subjects were six people who were selected using a purposive technique, six informants. This tourist destination is expected to be able to develop itself and explore the existing potential without forgetting and maintaining culture. Keywords: Tourism, Strategy Communicatioin, Belibak Village